Study of oxidation states of Fe- and Co-doped TiO2 photocatalytic energy materials and their visible-light-driven photocatalytic behavior. (14th June 2019) - Jaihindh, Dhayanantha Prabu; Verma, Atul; Chen, Ching-Cheng; Huang, Yu-Cheng; Dong, Chung-Li; Fu, Yen-Pei
Abstract: In this work we propose a study to determine the structure of Fe and Co doped TiO2 by using the Fe K-edge, Co K-edge and Ti K- edge X-ray absorption near edge spectroscopy. The detailed analysis of Fe and Co-doped TiO2 before and after Methylene blue (MB) treatment was examined under the irradiation of 35 W xenon arc lamp for 3 h. The materials treated with MB were studied by X-ray absorption spectroscopy, EPR and FT-IR which revealed that the oxidation state of Co 2+ was photo-oxidized to Co 3+ and Fe 3+ was photo-reduced to Fe 2+ or less. Thermodynamic, kinetic properties were studied at different reaction temperature and the activation energy (Ea ), enthalpy (ΔH), entropy (ΔS) and free energy (ΔG) of activation were calculated for the reaction. The activation energy has been found for TiO2, FeTiO2 and CoTiO2 as 24.771, 11.413 and 15.801 kJ mol −1 respectively. The structure, morphology and optical properties were studied by XRD, UV-diffuse reflectance spectra, FESEM, TEM and PL. Moreover, electrochemical studies were carried out to demonstrate the oxygen evolution reaction (OER) activity on TiO2, FeTiO2 and CoTiO2 in 1 M of H2 SO4 electrolyte, with a scan rate of 50 mV s −1 and the as-prepared photocatalysts could act as the promising electrode materials for water splitting. Graphical abstract: Image 1 Highlights: Thermodynamic including Ea, ΔH, ΔS and ΔG were calculated for the degradation. Fe-doped TiO2 at 40 °C showed good MB degradation reaction percentage of 94.93%. TiO2 doped with Fe 3+ and Co 2+ inhibits recombination.